AI Based Parkinson Disorder Diagnosis System – A Comprehensive Review - Anisha, C. D.; Arulanand, N. (Journal of Trends in Computer Science and Smart Technology, 2022)
Parkinson Disorder (PD) is a progressive neurological disorder. There is no specific and quantitative based PD diagnosis system. Artificial Intelligence (AI) is a tremendously growing technology, which aids in all sectors of healthcare. AI based PD diagnosis provides quantitative assessment more than subjective assessment, thereby providing robustness in diagnosis. This paper presents the review of Artificial Intelligence (AI) based PD diagnosis system. The conceptual framework for AI based PD diagnosis system, the challenges and future prospects in the domain of AI in PD diagnosis have been discussed.